Implementasi Nilai Nilai Dakwah pada Tradisi Bugis “Mabbaca Baca” di Desa Upang Ceria Kecamatan Muara Telang - Nurhalisa, Dian; Syarifudin, Achmad (CV. ITTC INDONESIA, 2025)
This study aims to describe and analyze the implementation of Islamic da’wah values in the Bugis tradition of Mabbaca Baca practiced in Upang Ceria Village, Muara Telang District. The Mabbaca Baca tradition involves the recitation of prayers and verses from the Holy Qur’an during special occasions such as weddings, thanksgiving ceremonies, and other customary events. This research employs a descriptive qualitative method, with data collected through observation, in-depth interviews, and documentation. The findings reveal that this tradition embodies da’wah values, including the values of faith (aqidah), Islamic law (sharia), and moral conduct (akhlaq), manifested through strengthening faith, applying Islamic teachings in daily life, and fostering behavior aligned with religious principles. The implementation of these values not only preserves local cultural heritage but also serves as a medium for religious guidance within the community. Thus, the Mabbaca Baca tradition plays a significant role in strengthening Islamic identity and maintaining social harmony among the Bugis diaspora.